2020
DOI: 10.1016/j.bpobgyn.2020.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Continuing the search for a hormonal male contraceptive

Abstract: This chapter discusses the mechanisms of action of hormonal male contraception, which suppresses the hypothalamic-pituitary-testis axis. When the intratesticular concentration of testosterone is subsequently suppressed to adequately low concentrations, spermatogenesis is arrested. Androgens are a necessary hormonal male contraceptive component because they not only suppress the hypothalamic-pituitary-testis axis, but also provide the male hormone necessary to maintain peripheral androgen functions. Past studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Clinically tested male OCPs included medroxyprogesterone acetate, norethisterone enanthate, testosterone enanthate, and testosterone undecanoate (Gava & Meriggiola, 2019). It was reported in clinical trials that androgens alone are less effective in suppressing spermatogenesis when compared with the combination of androgen and gonadotropin suppressive agents, for example, progestin (Yuen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically tested male OCPs included medroxyprogesterone acetate, norethisterone enanthate, testosterone enanthate, and testosterone undecanoate (Gava & Meriggiola, 2019). It was reported in clinical trials that androgens alone are less effective in suppressing spermatogenesis when compared with the combination of androgen and gonadotropin suppressive agents, for example, progestin (Yuen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, available male contraceptive pills are hormone-based . However, a safe, reversible, effective nonhormonal contraceptive is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, available male contraceptive pills are hormonebased. 26 However, a safe, reversible, effective nonhormonal contraceptive is needed. Future refinements through experimental structure−activity studies combined with computational modeling may help overcome potential limitations in vivo, such as absorption and the ability to cross the blood− testis barrier, paving the way for novel fertility regulators in men.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Progestin have been used in clinical as female contraception also experimenting to man since early 1970s. 17 Its mechanism might interfere hypothalamicpituitary-gonadal axis by suppressing gonadotropin release and impairing spermatogenesis. 8 Study indicated that progestin could became a potent inhibitor of LH and FSH which leading to improved sperm supperession.…”
Section: Testosterone and Progestin Combinations To Spermatogenic Sup...mentioning
confidence: 99%
“…20 A trial conducted that progestin/progestogen could suppress sperm production but lowering intratesticular testosterone concentration leading to androgen deficiency. 17 Androgen peripheral activity to other functions such as libido, erection, ejaculation and maintaining muscle mass would have agitated. Adding testosterone regimen into combinations is a compulsion to maintain these functions.…”
Section: Testosterone and Progestin Combinations To Spermatogenic Sup...mentioning
confidence: 99%